Pelatihan Test of English Proficiency bagi Dosen di Universitas Prof. Dr. Hazairin, SH Bengkulu - Elva Utami; Lisa Rakhmanina (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2019)
Workshop of Test of English Proficiency on Lecturers of Universitas Prof. Dr. Hazairin, SH Bengkulu This community service was aimed to improve the ability of the test of English proficiency (TOEP) the lecturers of Prof. Dr. Hazairin, SH University by practicing listening and reading skills. In addition, this activity was provided participants with insight into easy ways or tips and tricks when dealing with listening and reading questions in the TOEP with the aimed of increasing the participant's TOEP score. The method used was a lecture, discussion/question and answer, and practice. Participants who were the target of this training were lecturers who had not yet passed the lecturer certification. Pre-test at the beginning of the activity and post-test at the end of the activity carried out as an instrument for evaluating community service activities. The results of these community service activities indicated that there were differences in the ability scores of the trainees before and after the training. The pre-test results showed that the maximum score for TOEP was 405, the average score was 266.5 and the minimum score was 205. While the post-test results showed that the maximum score for participants' TOEP was 465, the average score was 393.5 and the minimum score was 360. Increasing the participant's TOEP score showed that the training activity was successful.